2022
DOI: 10.20944/preprints202206.0414.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optimizing Hyperparameters and Architecture of Deep Energy Method

Abstract: The deep energy method (DEM) employs the principle of minimum potential energy to train neural network models to predict displacement at a state of equilibrium under given boundary conditions. The accuracy of the model is contingent upon choosing appropriate hyperparameters. The hyperparameters have traditionally been chosen based on literature or through manual iterations. The displacements predicted using hyperparameters suggested in the literature do not ensure the minimum potential energy of the system. Ad… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The studies by Chadha et al 7 and He et al 34 demonstrated gradient computation and numerical integration through finite element SFs and Gauss quadrature. In this case, the spatial gradients are given by: bold-italicufalse(bold-italicXfalse)bold-italicXprefix≈bold-italicJprefix−1bold-italicϕbold-italicξ·bold-italicu,$$ \frac{\partial \boldsymbol{u}\left(\boldsymbol{X}\right)}{\partial \boldsymbol{X}}\approx {\boldsymbol{J}}^{-1}\frac{\partial \boldsymbol{\phi}}{\partial \boldsymbol{\xi}}\cdotp \boldsymbol{u}, $$ where bold-italicϕ$$ \boldsymbol{\phi} $$, bold-italicξ$$ \boldsymbol{\xi} $$, and bold-italicu$$ \boldsymbol{u} $$ denote the finite element SFs, natural coordinates, and displacement vector (evaluated at discrete nodes), respectively.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The studies by Chadha et al 7 and He et al 34 demonstrated gradient computation and numerical integration through finite element SFs and Gauss quadrature. In this case, the spatial gradients are given by: bold-italicufalse(bold-italicXfalse)bold-italicXprefix≈bold-italicJprefix−1bold-italicϕbold-italicξ·bold-italicu,$$ \frac{\partial \boldsymbol{u}\left(\boldsymbol{X}\right)}{\partial \boldsymbol{X}}\approx {\boldsymbol{J}}^{-1}\frac{\partial \boldsymbol{\phi}}{\partial \boldsymbol{\xi}}\cdotp \boldsymbol{u}, $$ where bold-italicϕ$$ \boldsymbol{\phi} $$, bold-italicξ$$ \boldsymbol{\xi} $$, and bold-italicu$$ \boldsymbol{u} $$ denote the finite element SFs, natural coordinates, and displacement vector (evaluated at discrete nodes), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The studies by Chadha et al 7 and He et al 34 demonstrated gradient computation and numerical integration through finite element SFs and Gauss quadrature. In this case, the spatial gradients are given by:…”
Section: Spatial Gradient Computation and Instabilitymentioning
confidence: 99%
See 3 more Smart Citations